Pascal’s theme of man and its development in existential philosophy - Zolkina, S. (Sententiae, 2000)
The article reconstructs the image of man in Pascal’s philosophy and compares it with the relevant themes of modern existential philosophy. The author identifies a number of key features of the image of man in Pascal’s philosophy: 1) the transience of human existence in the light of the infinity of the world; 2) the impossibility of human comprehension of infinity, which gives rise to man’s existential anxiety of, on the one hand, enclosure in his own existence and, on the other, dissolving in the infinity of the world; 3) man’s turning to knowing himself as a way to cope with such an anxiety. The author compares these features with the image of man in the existential philosophy of the twentieth century and argues that they are also characteristic of the latter. On this ground, the author states that Pascal’s doctrine and twentieth-century existential philosophy are related.